FEIJOADA AND SAMBA CONTEXTUAL ANALYSIS: IN AN ASSOCIATION IN A SUBURB IN RIO DE JANEIRO - Gabriella Fernandes Gachet; Marta Maria Antonieta de Souza; Mirian Ribeiro Baião (Universidade do Estado do Rio de Janeiro, 2016)
The study aims to analyse the sociocultural context of the dyad feijoada and samba in Cacique de Ramos, an association with 54 years of tradition in disseminating the traditional samba in the suburb in Rio de Janeiro. The study has drawn upon Depth Hermeneutics (DH) of Thompson (2011) with a view to the development of socio-historical analysis (SHA). Data were collected by means of free observation, formal and informal interviews, and internet searches. The elements that compose SHA were organized and treated as analytical categories, based on an adaptation of content analysis of Bardin (1977). The results pointed out that Cacique is a symbol of resistance and dissemination of samba carioca (from Rio), and it is the pride and joy of people who participate in and live next to the club. Shrouded in mysticism, the tamarind tree has become a symbol of identity, taking on the meaning of an almost sacred element, respect, blessing and good luck. The interactions among club-goers, neighbors, traders and Cacique de Ramos reveal the several power relations and the transmission of values among these subjects. Feijoada not only adds symbolism, but also serves as a resource of dissemination of cultural tradition, and helps to keep alive the samba circles and the association. DOI: 10.12957/demetra.2016.23541